TINJAUAN MAQASID SYARIAH TERHADAP PERTUKARAN KEWAJIBAN NAFKAH ANTARA SUAMI DAN ISTRI (Studi Kasus di Desa Karangsari Kecamatan Karanganyar Kabupaten Pekalongan) - Furqon, Muhammad (Al-Hukkam: Journal of Islamic Family Law, 2022)
In this study, we will discuss the practice of exchanging income obligations between husband and wife in Karangsari Village, and review the maqasid sharia of this practice. This research is a field research, and the approach used is a normative approach. Using two types of data, namely primary data and secondary data. The analysis technique uses qualitative techniques, starting with data collection, data reduction, data collection, and presentation of conclusions. The result of the research is that the exchange of the role of breadwinner between husband and wife is a solution to overcome the difficulties of the husband's lack of livelihood for the purpose of maintaining family integrity. The exchange of living obligations means that the husband is placed to take care of the house and children while the wife is the breadwinner working both inside and outside the home. In terms of qualification, the practice of maslahah can be related to maslahah dharuriyyah, namely primary benefits and maslahah hajiyyat, namely regarding the fulfillment of human needs, and relates to safeguarding the five points contained in maqasid sharia, namely hifdzun nasl and hifdzun mal because it is an effort to protect family and descendants. and maintain the family economy.